2008
DOI: 10.1182/blood-2008-01-133769
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat inhibits STAT6-mediated TH2 cytokine and TARC production and induces cell death in Hodgkin lymphoma cell lines

Abstract: Epigenetic changes have been implicated in silencing several B-cell genes in Hodgkin and Reed-Sternberg cells (HRS) of Hodgkin lymphoma (HL), and this mechanism has been proposed to promote HRS survival and escape from immunosurveillance. However, the molecular and functional consequences of histone deacetylase (HDAC) inhibition in HL have not been previously described. In this study, we report that the HDAC inhibitor vorinostat induced p21 expression and decreased Bcl-xL levels causing cellcycle arrest and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(138 citation statements)
references
References 33 publications
10
124
0
2
Order By: Relevance
“…Therefore, histone deacetylase inhibitors became attractive targets to treat HL. It has been demonstrated that in vitro vorinostat, in addition to its direct antitumor activity, alters cytokine balance and shifts toward a favorable Th1 composition through inhibiting STAT6 and decreasing TARC expression [94]. Vorinostat and romidepsin have been approved by the FDA in the treatment of relapsed cutaneous T cell lymphoma.…”
Section: Prospective Therapeutic Solutions and Possibilities Of Targementioning
confidence: 99%
“…Therefore, histone deacetylase inhibitors became attractive targets to treat HL. It has been demonstrated that in vitro vorinostat, in addition to its direct antitumor activity, alters cytokine balance and shifts toward a favorable Th1 composition through inhibiting STAT6 and decreasing TARC expression [94]. Vorinostat and romidepsin have been approved by the FDA in the treatment of relapsed cutaneous T cell lymphoma.…”
Section: Prospective Therapeutic Solutions and Possibilities Of Targementioning
confidence: 99%
“…STAT6 has been targeted in the setting of Hodgkin lymphoma via the histone deacetylase inhibitor, vorinostat. 32 This has been shown to inhibit STAT6 phosphorylation and was associated with a decrease in expression of chemokine Thymus and Activation-Regulated Chemokine and cytokine IL-5. Histone deacetylase inhibition is thought to exert antitumor effect via this immune regulation.…”
Section: Modern Pathology (2016) 29 570-581mentioning
confidence: 99%
“…1 Furthermore, epigenetic analyses are of interest since epigenetic therapy is emerging as a valuable and effective treatment approach for peripheral T-cell lymphomas and is also envisaged for Bcell and Hodgkin's lymphomas. [2][3][4][5] There are different sets of epigenetic instructions involved in the regulation of gene expression. 1 DNA methylation of gene promoters contributes significantly to gene silencing whereas histone modifications such as acetylation of lysine 9 and 14 of histone H3 (H3K9/14 acetylation) are positively correlated with gene activation.…”
Section: Introductionmentioning
confidence: 99%